Perancangan Sistem Informasi Surat Jalan dan Lembaran Permintaan Perbaikan (LPP) Berbasis Website di Gudang Spare Part PT Ban Indonesia - Gefallen; Ahmad Zohari; Choirunnisa, Anis; Putri, Tia Puspita (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2025)
PT Ban Indonesia faces challenges in managing delivery notes and Repair Request Sheets (LPP) in the spare parts warehouse, which are crucial for the smooth operation of production machines. The repetitive and non- integrated management process leads to inefficiency and potential errors. This study developed a web-based information system using Microsoft Visual Studio Code, the CodeIgniter framework, and MySQL database. The research results show that the designed web-based information system can improve time efficiency in managing delivery notes and LPP. This system successfully reduced the time required for document processing from an average of 160 seconds to 50.4 seconds. Consequently, there is a significant efficiency increase of 68.5%.